Preferensi Mahasiswa Terhadap Marketing Communication Mix - Wono, Hilda Yunita (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2018)
By using multiple marketing communication mix tools for private college probably spent expenses. The results of preference from students who have received various promotions and finally chose a X private college in Surabaya with the highest value of 9.05 is the existence of an expo or education exhibition since they at junior high school. Actively presentation about the benefits of an institution directly to the target market is the main preference of eleven (11) other marketing communication mix tools. Hopefully this research can be a reference for future promotion planning so much more effective in choosing a marketing communication mix tools that will use by X private college. Keywords: Preference, marketing communication mix, private college